Willingness of patients with cancer pain to participate in end-of-life decisions: a multi-center cross-sectional study from three coastal provinces in southern China - Xi Ke; Hongyu Zhu; Yu Zhang; Ling Yang; Simei Shi; Fang Zhu; Huiyu Luo (BMC Palliative Care, 2022)
Abstract Background Little is known about patients’ intention for participation in end-of-life decisions (EOLD) in three coastal provinces in southern China. This study aimed to explore the willingness of patients with cancer pain to participate in EOLD and potential influencing factors. Methods A multi-center cross-sectional study was performed in three coastal provinces in southern China. Two hundred and thirty patients with cancer pain were recruited and consented to fill out the questionnaires. The patients’ willingness to participate in EOLD, demographic and disease-related data was surveyed. Results In total, 223 patients completed and returned the survey (response rate = 96.95%). One hundred four cases (46.64%) were willing to participate in EOLD. 119 (54.36%) cases not willing to participate in EOLD, respectively. Multivariate logistic regression analysis shows that educational level (OR: 0.683, 95% CI: 0.482–0.966), history of alcoholism (OR: 8.353, 95%CI: 2.535–27.525), Eastern Cooperative Oncology Group (ECOG) score (OR: 0.645, 95% CI: 0.450–0.925) and experience of explosive pain (OR: 6.367, 95% CI: 3.103–13.062) and clinical rescue (OR: 3.844, 95% CI: 1.722–8.577) had significant effects on EOLD intention (P <  0.05). Finally, a predictive model combined above five factors was established, which showed a good discrimination (area under receiver operating characteristic curve: 0.849, 95% CI: 0.796–0.899, P <  0.001) and calibration (Hosmer-Lemeshow Test: Chi-square = 10.103, P = 0.258) for which patients more willing to participate in EOLD. Conclusions The willingness of patients with cancer pain to participate in EOLD is at a modest level in three coastal provinces in southern China. Patients with lower educational level, history of alcoholism, better health status and experience of explosive pain and clinical rescue may be more prone to participate in EOLD.